THE COORDINATES AND TYPOLOGY OF RELATIONSHIP BETWEEN THE PUBLIC SYSTEM AND THE DIFFERENT CATEGORIES OF STAKEHOLDERS - Florentina Neamtu; Luminita Zait (Studies and Scientific Researches: Economics Edition, 2013)
The development of the new information and communication technologies, which favored the modern societies transformation into knowledge-based society, forced a reconsideration of the governance principles based on what Abraham Lincoln said “Governance of citizens by citizens and for citizens''. The knowledge society coordinates raises new challenges for the public system, offering, at the same time, the opportunity to do activities more efficient and to development those approach that brings the citizen closer to public systems. Basically, by reconsidering and by emerging in the public system of concepts such as ethics, social responsibility and sustainable development it has been created the coordinates of oriented citizens implementation framework. Governments around the world are making significant efforts towards e-governance assimilation and implementation. These efforts are not focused only on the digitization process itself, but also target a broader reorganization of the public services process and of the participation processes based on the new information technologies. The article presents, based on a detailed analysis of the literature, different models that capture and define the relationships developed by public institutions with various categories of stakeholders.